The foration of signs in the litature of children by Mohammed Muwafaq selima - Majid, Sheikah Saoud (Arab Journal for Sciences and Research Publishing, 2019)
This study points out the structure signs in children's literature by Mohammed Mowafaq Salima and is divided into preface and two large parts.The preface deals with the signs and the children's literature، then introduces the writer and children's literature according to him.Then comes the first chapter which is entitled The first signs from (3- 7 years) in two subjects، the first one studies the language; the word، and the simple sentence. While the second subject deals with the image and includes the image function، the solidarity of the word and the image.The second chapter deals with signs and language، and includes two sections: the language which begins by studying syntax، and style with its characteristics. Followed by the second section which studies the structure of the sign and includes directly، and symbol. The research concludes with the third chapter، which deals with composite marks from (8- 12 years). It also includes two sections. The first section deals with the narration and the sign to study the structure of storytelling، personality، events، time، and place. The second section examines the theater and the sign in drama structure، conflict، drama character، time، and dramatic space.The conclusion then presents the results and recommendations.